Active cooling photovoltaic with IoT facility - Muhammad Nizam Kamarudin; Sahazati Md. Rozali; Mohd Saifuzam Jamri (Institute of Advanced Engineering and Science, 2021)
Harvesting energy from the sun makes the photovoltaic (PV) power generation a promising technology. To obtain a consistent state of charge (SOC), consistent energy must be harvested and efficiently directed to the battery. Overcharging or undercharging phenomena decreases the lifetime of the battery. Besides, the effect of irradiance toward solar in term of sunlight intensity effects the efficiency and hence, sluggish the SOC. The main problem of the solar panel revealed when the temperature has increased, the efficiency of solar panel will also be decreased. This manuscript reports the finding of developing an automatic active cooling system for a solar panel with a real time energy monitoring system with internet-of-things (IoT) facility. The IoT technology assists user to measure the efficiency of the solar panel and SOC of the battery in real time from any locations. The automatic active cooling system is designed to improve the efficiency of the solar panel. The effectiveness of the proposed system is proven via the analysis of the effect of active cooling toward efficiency and SOC of photovoltaic system. The results also tabulate the comparative studies of active-to-passive cooling system, as well as the effect of cooling towards SOC and efficiency of the solar panel.